Practical aspects of chimeric antigen receptor T-cell administration: From commercial to point-of-care manufacturing - Martinez-Cibrian, Nuria; Español-Rego, Marta; Pascal, Mariona; Delgado, Julio; Ortiz-Maldonado, Valentín (Frontiers in Immunology, 2022)
Chimeric antigen receptor T-cells targeting the CD19 antigen have achieved impressive results in patients with relapsed/refractory (R/R) B-cell malignancies, leading to their approval in the European Union and other jurisdictions. In Spain, the 100% academic anti-CD19 CART-cell product varnimcabtagene autoleucel (var-cel, ARI-0001 cells) has been extraordinarily approved under the Hospital Exemption clause for the treatment of patients older than 25 years of age with R/R acute lymphoblastic leukaemia. Var-cel has also been granted PRIority MEdicines designation by the European Medicines Agency for the same indication. In this review we reveal some practical aspects related to the preparation and administration of academic point-of-care CART-cell products, using var-cel as an example, and put them into the context of commercial products.